Effect of high dietary zinc oxide on the caecal and faecal short‐chain fatty acids and tissue zinc and copper concentration in pigs is reversible after withdrawal of the high zinc oxide from the diet. (April 2015) - Janczyk, P.; Büsing, K.; Dobenecker, B.; Nöckler, K.; Zeyner, A.
Summary: Zinc oxide (ZnO) used in high ('pharmacological') levels to prevent diarrhoea in pigs is assumed to reduce copper (Cu) in tissues and inhibits large intestinal microbial fermentation. To test it, German Landrace pigs were weaned on d28 of age and fed diets containing either 100 (LowZinc, LZn, n = 10) or 3100 mg ZnO/kg (HighZinc, HZn, n = 10). The mixed feed (13.0 MJ ME, 18.5% crude protein) was based on wheat, barley, soya bean meal and maize. After 4 weeks, the HZn group was further fed 100 mg ZnO/kg for another 2 weeks. Caecal contents, faeces and tissues were collected after 4 weeks ( n = 5 and n = 10 respectively) and 6 weeks ( n = 5 and n = 5 respectively). Faeces and caecal content were analysed for dry matter (DM), pH, ammonia, lactic acid (LA) and short‐chain fatty acids (SCFA) on native water basis.anova was performed to elucidate significant differences at p < 0.05. No diarrhoea occurred. After 4 weeks, the caecal contents' pH increased (p < 0.001) and butyric (p < 0.05) and valeric acid (p < 0.01) decreased in the HZn group in comparison with LZn. In faeces, a decrease of acetic (p = 0.009), butyric (p = 0.007) and valeric acid (p = 0.046), as well as reduced acetic:propionic acid (A:P) ratio (p = 0.025) was observed in the HZn group in comparison with LZn. Faecal ammonia decreased in HZn (p = 0.018). No differences (p > 0.05) were recorded in caecal contents after 6 weeks. In faeces, acetic acid remained lower in the HZn group in comparison with LZn (p = 0.006), as did the A:P ratio (p = 0.004). Zn concentration in liver, kidneys and ribs, and Cu concentrations in kidneys increased in HZn. Withdrawal of ZnO resulted in reversibility of the changes. The effect on butyric acid should be discussed critically regarding the energetic support for the enterocytes. High Zn and Cu tissue concentrations should be considered by pet food producers.